Modeling an Alternative Benchmarking for Home Financing: A Comparative Analysis between Malaysia and the United Kingdom - Mohd Yusof, Rosylin; Kassim, Salina; Abd. Majid, M. Shabri; Hamid, Zarinah ([s.n.], 2009)
This study attempts to model retail property rents in the property sector in both Malaysia and the United Kingdom. Essentially, this study examines the determinants of retail property rents in order to come up with the rental values to be benchmarked against the rate of profits of home financing, thus providing an alternative to the current practice of relying on the conventional interest rates to price Islamic home financing products. In the quest of modeling an alternative benchmarking for the Islamic home financing product, this study explores the possibility of rental to replace the current conventional interest rates. With the sophistication, proliferation and diversity of instruments in the global Islamic banking and finance industry, the development of an alternative benchmark can serve as a catalyst for a more rapid pace of the development in this industry. This study therefore compares two models comprising the lending rate and rental price as the dependent variables and relevant macroeconomic variables, namely GDP, CPI, REER and TBR as the independent variables and analyses the short and long-run dynamics between these variables. The analysis which starts with the long-run ARDL estimates find that for the case of Malaysia, rental price is significantly affected by the interest rate and income level, while the lending rate is significantly affected by the interest rate and exchange rate. For the case of UK, the results show that only the rental price shows significant relationship with the macroeconomic variables, while lending rate does not have any significant relationship with the macroeconomic variables. In general, our results suggest that in the long run, the average rental prices in both Malaysia and the UK are truly reflective of the macroeconomic condition compared to the lending rate. The finding that the rental prices being significantly affected by TBR in the long run is consistent with the fundamental theory of demand that income and substitution effects influence the rental prices for the properties or houses. The TBR is regarded as an alternative investment for buying a house. An increase in the TBR negatively affects the rental price such that when interest rate rises, the return to investment in interest-bearing instrument increases, thus reducing the demand to rent and own houses. However, GDP is found to affect only the average rental prices in Malaysia. These findings lend support to fundamental economic theory which states that income and substitutes affect the demand for houses and in turn affect the rental values. The next test involves the causality analysis based on the short run bivariate Granger causality test and multivariate causality test based on the VECM. For the case of Malaysia, the short run bivariate causality analysis suggests a significant causality running from GDP to the lending rate, while there is no significant causality running from any of the macroeconomic variables to rental price. For the case of the UK, however, the short run bivariate causality suggests that rental price is caused by CPI and exchange rate, while none of the macro-variables significantly causing the lending rate. In this regard, the short run causality provides a contradictory result between Malaysia and the UK. Moving on to the long-run multivariate causality based on the VECM, findings for both Malaysia and the United Kingdom conclude that all the macroeconomic variables are significant in causing the average rental price as reflected by the significant ECT. It suggests that all the macroeconomic variables adjust towards long run equilibrium when rental price is the dependent variable. This implies that in the long run, the macroeconomics variables can be used to predict the rental price. In contrast, none of the macroeconomic variables are significant in causing lending rate in the long run. The results of further testing suggest similar findings within the context of short run framework. For the case of Malaysia, the variance decomposition analysis suggests that in the short run, rental price is insignificantly affected by the macroeconomic variables, while lending rate tends to be more sensitive to changes in macroeconomic variables in the short run. The VDC analysis for Malaysia reveals that rental prices seem to be insignificantly affected by macroeconomic variables. This further explains the possibility of other factors like the individual characteristics of the houses affecting the rental price in short run. Unlike Malaysia, the VDC analysis for the UK indicates that variations in rental price are significantly contributed by changes in CPI and REER. This implies that the relative exogeneity of inflation as the most significant variable in explaining the fluctuations in rental prices in the UK. Our IRFs analysis provides a further insight on the short run dynamics between the macroeconomic variables between the countries. The IRFs suggest that no significant effect is found between the shocks in the macroeconomic variables and the innovation in the average rental price in the short-run. In addition, the IRF functions indicate the significance of TBR in affecting rental price in the first two months. It could be inferred that the change in TBR has almost instantaneous impact on the rental price in the short run. In short, the findings can be summarized into two dimensions. First, in terms of time dimension, the results suggest that lending rate is sensitive to the macroeconomic variables in the short run, while in the long run, the rental price is more truly reflective of the macroeconomic conditions. Second is in terms of the maturity of the property market., The study shows that rental price can be sensitive to changes in the macroeconomic conditions in a more matured market (i.e. the UK) than in a less matured market (i.e. Malaysia).